2018
DOI: 10.1590/1678-5150-pvb-5300
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of mesenchymal stem cell-specific proteins in adipose tissue-derived cells: possible immunosuppressing agent in partial allograft for restoring the urinary bladder in rabbits

Abstract: Adipose tissue-derived stem cells (ADSCs) are an attractive source of mesenchymal stem cells (MSCs) for use in tissue engineering and clinical applications. This paper focuses on the characterization of ADSCs used as immunosuppressive agent in rabbits undergoing partial allograft for urine bladder restorage. For this study highlighted the characterization of the ADSCs used as immunosuppressive agents in rabbits submitted to partial allograft for restoration of the urinary vesicle, using 25 animals, six months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Flow cytometry analysis revealed that the ADSCs at the first passage could express the MSC-specific markers (CD105 and CD90) well, and the expressions of the hematopoietic markers (CD45 and CD34) were at a low level. 5,62 Fig. 1E and F show the Alizarin Red S and Oil Red O staining after 21-days of culturing in osteogenic and adipogenic mediums.…”
Section: Adsc Characterizationmentioning
confidence: 99%
“…Flow cytometry analysis revealed that the ADSCs at the first passage could express the MSC-specific markers (CD105 and CD90) well, and the expressions of the hematopoietic markers (CD45 and CD34) were at a low level. 5,62 Fig. 1E and F show the Alizarin Red S and Oil Red O staining after 21-days of culturing in osteogenic and adipogenic mediums.…”
Section: Adsc Characterizationmentioning
confidence: 99%